Evaluation of Medication Adherence among Patients with Chronic Kidney Disease in a Tertiary Healthcare Hospital (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Chronic kidney disease (CKD) is characterized by progressive renal function decline, leading to metabolic imbalances and uremia. Medication adherence is defined as ‘the extent to which the patient’s behavior matches agreed recommendations from the prescriber. The pill burden in CKD patients is high because on average, they have to take around 8–10 tablets per day due to co- morbidities and dominant risk factors of CKD. This study aims to assess medication adherence among CKD patients and analyze factors affecting non- adherence. The 8-item Morisky Medication Adherence Scale (MMAS) was employed to gauge adherence in 142 CKD cases. Findings revealed that most patients were males within the age range of 51-60 years, predominantly smokers (36.61%) and affected by comorbidities such as hypertension (37.32%) and diabetes (21.83%). The majority were illiterate (77%), and low adherence (63.38%) was prevalent, while medium (30.28%) and high adherence (6.33%) levels were also observed. Educational status, social habits, and comorbidities influenced adherence, with education positively impacting adherence. Males exhibited higher CKD prevalence, and geriatric patients were more affected. Smoking habits and comorbidities like hypertension and diabetes negatively influenced adherence. Proper interventions and counseling strategies could enhance CKD patients' medication adherence.
Keywords: Diabetes Mellitus; Medication Adherence; Patient Counselling; Pharmacist Intervention; Treatment Compliance; Glycemic Control